2016
DOI: 10.1016/j.cemconres.2015.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Physico-chemical interaction between mineral admixtures and OPC–calcium sulfoaluminate (CSA) cements and its influence on early-age expansion

Abstract: The present study aims at examining the physico-chemical factors influencing the expansion characteristics of OPC-CSA blend in the presence of mineral admixtures. Three different admixtures: Class ‗F' fly ash (‗F'FA), Class ‗C' fly ash (‗C'FA) and silica fume (SF) were used as 15%, 15% and 5% replacement of total cementitious binder. Longitudinal expansion of cement pastes prepared at w/cm-0.44 showed that the Class ‗F'FA increased the expansion whereas the Class ‗C'FA and SF reduced the expansion. The pore so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(22 citation statements)
references
References 61 publications
(77 reference statements)
1
19
0
Order By: Relevance
“…Thus, sample C showed the strongest peaks of monosulfate and kuzelite, whereas the RO sample showed the strongest peaks of Friedel's salt in the XRD results, particularly at 28 days. In addition, in all samples without gypsum, despite the small amount of calcium sulfate (~0.7 wt%) in the CSA cement of this study, ettringite (Ca 6 Al 2 (SO 4 ) 3 (OH) 2 •26H 2 O) was also identified, although its XRD peaks were relatively weak, a result similar to those found in earlier studies [36][37][38].…”
Section: Xrdsupporting
confidence: 89%
“…Thus, sample C showed the strongest peaks of monosulfate and kuzelite, whereas the RO sample showed the strongest peaks of Friedel's salt in the XRD results, particularly at 28 days. In addition, in all samples without gypsum, despite the small amount of calcium sulfate (~0.7 wt%) in the CSA cement of this study, ettringite (Ca 6 Al 2 (SO 4 ) 3 (OH) 2 •26H 2 O) was also identified, although its XRD peaks were relatively weak, a result similar to those found in earlier studies [36][37][38].…”
Section: Xrdsupporting
confidence: 89%
“…• Densification of the microstructure; similar to what observed with the reactions of SCMs at advanced ages in the OPC system, the space occupied by the water at the beginning is gradually filled by hydrates which limits further hydration [130][131][132].…”
Section: Silicate Aluminate Interactionsmentioning
confidence: 57%
“…The refined parameters included phase scale factors, background coefficients, zero-shift error, lattice parameters, peak shape parameters, and preferred orientation, if needed. As for reliability of the data, with the software’s “goodness of fit” setting fixed to <4, the fitted curve matched well with the raw data [23,24,25].…”
Section: Methodsmentioning
confidence: 80%